New Zealand : Financial Sector Assessment Program: Technical Note-Macroprudential Institutional Framework and Policies. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note assesses the macroprudential institutional framework and policies in New Zealand. New Zealand has a strong institutional framework for macroprudential policy. This framework is based on a clear mandate for financial stability operationally clarified by a memorandum of understanding. The Reserve Bank of New Zealand is the single prudential regulator with responsibility and authority for supervision of financial institutions and macroprudential policies. A clear mandate for financial stability, independent decision making, transparent communication, and external accountability form the basis of the strong framework that was put in place. Institutional arrangements could be strengthened further by making the procedures to adjust the macroprudential framework more transparent.